Developing a framework for prefabrication supply chain integration in New Zealand using blockchain technology : a thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, Construction Project Management, School of Built Environment, College of Sciences, Massey University, Auckland, New Zealand - Bakhtiarizadeh, Ehsan (Massey University, 2024)
Prefabrication or off-site fabrication in New Zealand is snowballing in terms of its contribution to the delivery of construction projects. The increasing demand for new houses and the lack of affordable accommodations in New Zealand evolved the need for innovative and effective project delivery systems instead of conventional types. The prefabrication sub-sector is considered leverage for eliminating the shortcomings of traditional construction systems. However, this sub-sector of the construction industry struggles with challenges such as low coordination and integration across its supply chain partners. These challenges are attributed to the inefficient foundation of communication and information flow. This research addresses the problem of the relatively weak integration within New Zealand's prefabrication construction supply chain. The particular focus of the study is on information integration. The central point is that an effective and efficient exchange of information among supply chain stakeholders is imperative for enhancing supply chain integration in New Zealand's highly fragmented construction industry. Therefore, this study concludes that providing an effective information-integration-based platform for stakeholders involved in prefabrication projects will deliver integration improvement in the whole supply chain system. Blockchain technology, as a secure information integration instrument, capably improves the integration of information flow within the prefabrication sub-sector. Blockchain, a decentralised, safe, and unalterable information storage, offers numerous benefits to investors, clients, end-users, and other organisations or individuals. This technology, via its inherent features such as decentralisation, consensus mechanism, and immutability, supports organisations engaged in the supply chain with more transparent and trustful interactions and information flow. By adopting qualitative and quantitative data collection methods, this research provides insight into the applicability of blockchain technology within prefabrication construction supply chains. Minimum input requirements for blockchain according to types and patterns of information will be identified and categorised, and an applicable framework for using this new information integration technology will be proposed. Some key findings of this study are the identification and classification of (1) key stakeholders and recent project phases within the prefabrication supply chain, (2) flow of information across the stakeholders in different project phases, (3) important information attributes, (4) communication channels among stakeholders, and (4) impact of blockchain technology on facilitating information integration in the prefabrication construction industry of New Zealand. This research utilised pilot interviews, a questionnaire survey, a focus group study, and a validation survey to verify the objectives of the research and validate the proposed blockchain-based framework. The findings of this research could also be relevant to other industries facing similar challenges that rely heavily on information inputs. By identifying the importance of efficient information integration and the attributes crucial for successful project outcomes, stakeholders can prioritise investments in technologies like blockchain to streamline communication and data sharing across the supply chain. The identification of conventional communication modes like email, meetings, and internet-based applications in the prefabrication supply chain suggests a reliance on traditional methods for information exchange. However, the research underscores the importance of transparency, traceability, and reliability in communication, especially in the context of advanced information technology adoption. This implies a need for stakeholders to develop tailored communication strategies that leverage both conventional methods and emerging technologies to ensure effective collaboration throughout project phases. Finally, the development of a practical document management framework utilising blockchain technology presents opportunities for innovation and collaboration within the prefabrication industry. By demonstrating the applicability of blockchain in addressing document management challenges and validating the framework through expert feedback, the research paves the way for industry practitioners to adopt similar approaches in their projects. This suggests a broader trend towards embracing digital solutions and collaborative platforms to enhance information exchange, transparency, and project efficiency in the prefabrication sector.
Keywords: Business logistics; Technological innovations; Prefabricated house industry; Management; New Zealand; Blockchains (Databases); prefabrication, supply chain integration, blockchain technology; 330206 Building science, technologies and systems; 350909 Supply chains